Effects of Fagopyrum dibotrys rhizoma meal supplementation on productive performance, egg quality, egg nutritional value, and serum biochemical parameters of Shanma laying ducks - Xiong, Pingwen; Ai, Gaoxiang; Chen, Jiang; Song, Wenjing; Su, Weide; Yu, Dongyou; Song, Qiongli; Xu, Chuanhui; Zou, Zhiheng; Wei, Qipeng; Chen, Xiaolian; Hu, Lizhen (Frontiers in Veterinary Science, 2025)
IntroductionThe rhizoma of Fagopyrum dibotrys (D. Don) Hara, a traditional natural medicinal herb with extensive historical applications in China, possess anti-inflammatory, anticancer, antioxidant, antimicrobial, immunomodulatory, and antidiabetic effects. However, the potential positive effects of F. dibotrys rhizoma meal (FDRM) on productive performance in high-density laying duck farming remain unclear. This experiment was conducted to assess the impacts of FDRM supplementation in Shanma laying ducks diet by determining productive performance, egg quality, egg nutritional value, and serum biochemical parameters.MethodsWith similar laying performance (80.88 ± 5.17%) and body weight (1.24 ± 0.02 kg), 512 healthy 32-week-old Shanma laying ducks were randomly assigned to four groups consisting of eight replicates (16 ducks per replicate). Ducks in the control group (F0 group) were fed only the basal diet, while the other groups (F1, F2, and F3 groups) were fed the basal diets supplemented with 1, 2, and 3% FDRM, respectively. The experiment lasted for 49 days with ad libitum access to feed and water.ResultsThe results showed that supplementing FDRM in duck diet had no adverse effects on laying performance (p > 0.05). Additionally, compared with the control group, dietary supplementation with FDRM significantly improved the shell strength, yolk color, and shell proportion (p < 0.05), while increasing the serum total protein (TP) content (p < 0.05). The study also found that adding 2% FDRM significantly enhanced the contents of total amino acids, essential amino acids, and umami amino acids in eggs (p < 0.05), improved the composition of monounsaturated fatty acids and polyunsaturated fatty acids (p < 0.05), and reduced the saturated fatty acids content. However, 3% FDRM addition increased the serum blood urea nitrogen content (p < 0.05), indicating reduced the dietary protein utilization efficiency.DiscussionWith the rapid development of the economy and the continuous improvement of people’s living standards, people have raised higher demands for the nutritional and high quality of eggs. Duck eggs, rich in protein, amino acids, fatty acids, minerals, and vitamins, serve as an important source of high-quality protein for human’s food and health. Moreover, the n-3 polyunsaturated fatty acids in eggs have beneficial effects in preventing cardiovascular diseases. Currently, numerous studies have shown that F. dibotrys is abundant in active substances such as flavonoids and phenolics. Additionally, Traditional Chinese herbs rich in flavonoids and phenolics have been proven to enhance the nutritional value of eggs, improve the laying performance of poultry, and promote their overall health. This study indicated that dietary supplementation with 2% FDRM might improve egg quality and egg nutritional value of Shanma laying ducks through improving the shell strength, yolk color, and shell proportion, enhancing yolk fatty acids and amino acids profiles and elevating serum TP content.